“Self-Fashioning”: Female Chinese International Students Navigating United States Campuses - Huang, Ting; Khan, Shadeed (Journal of International Students, 2024)
Research on international students’ integration into Western campuses tends to find that female international students may experience more difficulty in adjusting to new cultures than their male counterparts (Contreras-Aguirre & Gonzalez, 2017; Manese et al., 1988; Mallinckrodt & Leong, 1992). Few researchers have delved into what female Chinese international students have to offer. Using a phenomenological study frame and a critical and interpretative lens to conduct detailed interviews, this study explored how a group of Chinese female international students self-fashioned during these experiences navigating the U.S. study. Three major themes emerged in our female Chinese international students’ stories: their “self-fashioning” helps them (1) sophistically navigate the U.S. system better, (2) tactically fit into the new U.S. society, and (3) adaptively create more genuine personal identities. Implications were discussed at the end of this study.